Radiosurgery with Helical Tomotherapy: Outcomes for Patients with One or Multifocal Brain Metastasis. (December 2015) - Barra, Salvina; Agostinelli, Stefano; Vagge, Stefano; Giannelli, Flavio; Siccardi, Desiderio; Garelli, Stefania; Aloi, Deborah; Belgioia, Liliana; Bosetti, Davide; Zeverino, Michele; Corvò, Renzo
To evaluate the feasibility and report the preliminary results for stereotactic radiosurgery (SRS) treatments of single or multiple brain metastases delivered with helical tomotherapy (HT) by means of the InterFix™ Radiosurgery kit. Between September 2010 and August 2012, thirty patients underwent SRS for treatment of 46 brain metastases with a median prescription dose of 20 Gy (range 15-21 Gy). Clinical response was assessed with 2-3 month intervals by magnetic resonance imaging (MRI). Dose distribution indexes were computed and compared with published data for SRS performed with dedicated machines. After a median follow-up of 14 months (range 4-31) the estimated overall survival (OS) rate was 70% at 6 months, 60% at 12 months and 44% at 18 months. Local control (LC) was 72% at 6 months, 65% at 12 months and 50% at 18 months. Acute toxicity as headache and epileptic crisis occurred in only two patients. The mean values of conformity, homogeneity and gradient score indexes were 1.36, 1.04 and 50 respectively. HT-SRS for single or multiple brain metastases appears a reliable technique with encouraging clinical outcomes and competitive dosimetrical results.